Development and optimization of a fentanyl pharmacokinetic model for target-controlled infusion in anaesthetized dogs. (January 2023) - Cattai, Andrea; Merlanti, Roberta; Bizzotto, Roberto; Lucatello, Lorena; Capolongo, Francesca; Franci, Paolo
Abstract: Objective: To investigate pharmacokinetics (PK) of fentanyl administered by target-controlled infusion (TCI), and to develop a PK model optimized by covariates for TCI in anaesthetized dogs. Study design: Prospective clinical study. Animals: A group of 20 client-owned dogs with spinal pain undergoing anaesthesia for magnetic resonance imaging. Methods: Fentanyl was administered as an infusion to 20 anaesthetized dogs using a TCI system incorporating a previously described fentanyl two-compartment PK. Arterial blood samples were collected at specific time points during the infusion and over 60 minutes post-infusion for measurement of fentanyl plasma concentrations. The predictive performance of the Sano PK model was assessed by comparing predicted and measured plasma concentrations. A population PK analysis was then performed using a nonlinear mixed-effect modelling approach, allowing inter- and intra-individual variability estimation. Finally, a quantitative stepwise evaluation of the influence of various covariates such as weight, body condition score, size, size-related age, sex and type of premedication on the PK model was considered. Results: Overall predictive performance of the Sano PK set of variables was not clinically acceptable in anaesthetized dogs. Fentanyl PK was best described by a three-compartment model. Weight and sex were found to affect the volume of distribution of the central compartment. Addition of these two covariate/variable associations resulted in a reduction of the objective function value (OFV) from –340.18 to –448.34, and of the median population weighted residual and the median population absolute weighted residual from 16.1% and 38.6% to 3.9% and 20.3%, respectively. Fentanyl infusions at measured concentrations up to 5.4 ng mL –1 in sevoflurane-anaesthetized dogs resulted in stable anaesthesia and smooth recoveries without complications. Conclusions and clinical relevance: A population three-compartment PK model for fentanyl TCI in anaesthetized dogs was developed. Weight and sex have been detected and incorporated as significant covariates.